Cross-Generational Perception Analysis of the Role of Sharia Economics in Reducing Social Inequality in Jakarta (Case Study of Gen Z, Gen Y, Gen X, and Early Gen X) - Hadi, Kuncoro; Nuraini, Nuraini (UI Scholars Hub, 2024)
This study aims to analyze cross-generational perceptions of the role of Islamic economics in reducing social inequality in Jakarta. Using a quantitative approach, this study collected data from 994 respondents divided into four age groups (18-25 years, 26-35 years, 36-45 years, and 46-55 years). Data were analyzed using the Kruskal-Wallis test to evaluate differences in perceptions between age groups on the basic principles of Islamic economics, the fairness of the system, and the effectiveness of its implementation. The results showed significant differences in understanding and perception between age groups, with 26-35 years old having the highest level of understanding. The findings provide important insights for policymakers to design more inclusive education strategies and improve the implementation of Islamic economics in urban communities. This research makes a novel contribution to the literature on Islamic economics by integrating cross-generational analysis in the context of reducing social inequality.